Affective Meaning, Concreteness, and Subjective Frequency Norms for Indonesian Words - Sianipar, Agnes; van Groenestijn, Pieter; Dijkstra, Ton (Frontiers in Psychology, 2016)
This study investigated the lexical-semantic space organized by the semantic and affective features of Indonesian words and their relationship with gender and cultural aspects. We recruited 1,402 participants who were native speakers of Indonesian to rate affective and lexico-semantic properties of 1,490 Indonesian words. Valence, Arousal, Dominance, Predictability, Subjective Frequency, and Concreteness ratings were collected for each word from at least 52 people. We explored cultural differences between American English ANEW, Spanish ANEW, and the new Indonesian inventory (called CEFI). We found functional relationships between the affective dimensions that were similar across languages, but also cultural differences dependent on gender.